El desarrollo de la motricidad gruesa en niños de 4 a 5 años a través de las artes escénicas. - Talavera Tipán, Narcisa Pilar (2020)
The present research work has the purpose of carrying out a study about the development of gross motor skills in children from 4 to 5 years of age and how this aspect can be addressed from the performing arts as strategies for the consolidation of motor activities allowing the reduction of the energy accumulated in children after performing motor activities. To determine the problem, data collection instruments were applied, such as observation guides applied to the children and surveys directed to the teachers of the initial level, which showed that the level of gross motor skills in children is low, so their development and agility motor are affected; Likewise, the survey addressed to the teachers allowed us to verify that the activities carried out tend to be repetitive and monotonous and do not effectively develop the motor aspect, therefore, through the present work it is intended to strengthen the development of gross motor skills considering the arts performances as an alternative for which a playful strategy guide developed in sessions for the development of gross motor skills was developed in order to address activities for the motor development of children in a more complete and effective way.